Arabic for Specific Purposes in Islamic Higher Education: Systemic Learning Challenges among Non-Pesantren Students - A. Gazali; Nihayatur Rahmah; Roychan Yasin; Muhammad Ridwan; Alya Raihana Sari (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2026)
Arabic competence is essential in Sharia Accounting programs for accessing Islamic legal sources and disciplinary terminology. However, non-pesantren students often face persistent difficulties due to limited prior exposure and misaligned instructional practices. This study investigates the systemic challenges of Arabic language learning among non-pesantren students in the Sharia Accounting Program at the State Islamic University of Madura. Using a qualitative descriptive approach, data were collected through classroom observations, semi-structured interviews, and document analysis, and analyzed through triangulation. The findings reveal that learning challenges are structural in nature and arise from the interaction of three dimensions: linguistic–cognitive limitations, affective disengagement, and pedagogical–institutional mismatch. Instructional designs that assume prior Arabic competence increase cognitive load, limit communicative development, and indirectly generate anxiety and low motivation. The significance of this study lies in its contribution to understanding Arabic learning difficulties as a systemic issue rather than an individual deficit, providing empirical evidence to inform curriculum alignment, pedagogical reform, and the development of Arabic for Specific Purposes (ASP) in Sharia Accounting within Islamic higher education.